Entre o p??tio e a sala de aula: malha????o na tela e na escola - Assis, Silvia Regina de (2008)
This paper enquires into the cultural relationship teenagers have with the soap opera Malha????o, and elements of projection and identification triggered by this fictional genre in pupils from a public school located in the S??o Paulo metropolitan area. Ages range from 14 to 18 years old. This study tries to articulate the relationship between academic knowledge and youth life experience, since both aspects are present in the pupil. The study is based on the work of various authors and some ideas from Edgar Morin s thoughts on complexity, which allow us to comprehend the multidimensionality existing between systematic knowledge and life experience, which are understood as complementary, mutually reinforcing and influencing each other. It also establishes the relationship between the different ways of producing knowledge, giving equal importance to knowledge acquired from TV fiction and daily life as to that acquired in the academic context, as they jointly comprise youth culture. In doing so, it aims at enriching learning deriving from the interaction of knowledge from different cultures: the scientific, humanist and popular cultures. The data from the field study show the cultural relationship teenagers have with the soap opera Malha????o, revealing that the imaginary activities not only refer to the imaginary and fabulation systems, they also nurture emotional life and penetrate practical life through the adolescents projections and identifications with aspects found in the soap opera. We found that, through the subject matter dealt with in the plots in Malha????o, the teenagers can produce knowledge, acquire information and appropriate attitudes and ideas that, at times, they try to transfer to situations in their own lives. This work offers routes to a possible rational and sensitive pedagogical praxis, capable of associating different languages, such as bringing TV images to the classroom, since they are present among teenagers even after the time of watching, becoming something that extends into everyday life.